Relatives in silent kidney disease screening (RISKS) study: A Chinese cohort study. (20th November 2017) - Li, Philip Kam‐Tao; Ng, Jack Kit‐Chung; Cheng, Yuk Lun; Kwan, Tze Hoi; Leung, Chi Bon; Lau, Miu Fong; Choi, Koon Shing; Fung, Samuel Ka‐Shun; Ho, Yiu Wing; Mak, Siu Ka; Tang, Sydney Chi‐Wai; Wong, Kin Shing; et al.
Summary at a Glance: The authors studied 844 asymptomatic first‐degree relatives of patients in different stages of chronic kidney disease (CKD). They concluded that relatives in all stages of CKD were at risk of CKD and identified risk factors which predicted kidney damage. ABSTRACT: Aim: Family members of patients with end‐stage renal disease (ESRD) have higher risk for chronic kidney disease (CKD). Limited study has examined the risk of developing CKD in relatives of patients in earlier stages of CKD. Methods: From January 2008 to June 2009, the Hong Kong Society of Nephrology studied first‐degree relatives of stage 1–5 CKD patients from 11 local hospitals. A total of 844 relatives of 466 index CKD patients (stages 1–2: 29.6%; stage 3: 16.7%; stage 4: 10.9%; stage 5: 42.7%) were reviewed for various risk factors of CKD. We also defined a composite marker of kidney damage by the presence of one or more following features: (i) positive urine protein, (ii) spot urine protein‐to‐creatinine ratio ≥0.15 mg/mg, (iii) hypertension and (iv) estimated glomerular filtration rate (eGFR) ≤60 mL/min per 1.73 m 2 and determine its association with participant and index patient factors. Results: Among these 844 relatives, 23.1%, 25.9% and 4.4% of them had proteinuria (urine protein ≥1+), haematuria (urine red blood cell ≥1+) and glycosuria (urine glucose ≥1+), respectively. Proteinuria ( P  = 0.10) or glycosuria ( P  = 0.43), however, was not associated with stages of CKD of index patients. Smoking participants had a significantly lower eGFR (102.7 vs. 107.1 mL/min per 1.73 m 2 ) and a higher prevalence of proteinuria (33.6% vs. 21.4%). Multivariate analysis showed that older age, male gender, obesity, being parents of index patients and being the relatives of a female index patient were independently associated with a positive composite marker. Conclusion: First‐degree relatives of all stages of CKD are at risk of developing CKD and deserve screening. Parents, the elderly, obese and male relatives were more likely to develop markers of kidney damage.